Role of the Literature in ELT Course of Mid-Western University - Bist, Resham Bahadur (Journal of NELTA Surkhet, 2018)
This article identifies the role of literature course included in B.Ed. English Curriculum of Mid-Western University for the promotion of language skills and areas. It begins with the general introduction of literary course either it supports to EFL/ESL context. The research questions and objectives are set to examine the role of literature course in ELT classroom. Then it is closely observed literature contents in B.Ed. English curriculum. It is discussed via self-inspection and reflection of my own experience. It reaches in conclusion that literary texts provide rich linguistic input and effective stimuli for students to express themselves, and a potential source of learner motivation. These texts also provide an opportunity for multi-sensorial classroom experiences and can appeal to learners with different learning style. The students can promote their creativity and language proficiency in ESL/EFL context of ELT classroom. Therefore, it is essential to design the literary texts in ELT course to promote both the language skills (i.e. listening, speaking, reading, and writing) and language areas (i.e. vocabulary, grammar, and pronunciations). Journal of NELTA Surkhet, Vol. 5 January, 2018, Page: 56-64